Acute Cauda Equina Syndrome Due to Spondylolisthesis in the Midst of a Pandemic: A Case Report. Issue 1 (10th January 2022) - Isakov, Aleksandr; Yanamadala, Vijay; Yassari, Reza; Udemba, Adaobi; Shaparin, Naum; Hascalovici, Jacob R.
Abstract : Case: A 54-year-old woman with chronic lumbar radiculopathy due to grade II spondylolisthesis at lumbar 4 to 5 developed acute cauda equina syndrome (CES) after an elective lumbar decompression, and fusion was delayed because of statewide bans on elective procedures during the pandemic. The diagnosis was made largely through telehealth consultation and eventually prompted urgent neurosurgical intervention. Conclusion: This case report illustrates a rare presentation of acute CES and highlights some of the challenges of practicing clinical medicine in the midst of a pandemic.